2018
DOI: 10.1155/2018/3989201
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-Aspartate Receptors Involvement in the Gentamicin-Induced Hearing Loss and Pathological Changes of Ribbon Synapse in the Mouse Cochlear Inner Hair Cells

Abstract: Cochlear inner hair cell (IHC) ribbon synapses play an important role in sound encoding and neurotransmitter release. Previous reports show that both noise and aminoglycoside exposures lead to reduced numbers and morphologic changes of synaptic ribbons. In this work, we determined the distribution of N-methyl-D-aspartate receptors (NMDARs) and their role in the gentamicin-induced pathological changes of cochlear IHC ribbon synaptic elements. In normal mature mouse cochleae, the majority of NMDARs were distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…Although we did not observe significant synapse degradation/loss, we did observe changes in ABR wave III/I ratios indicating physiological changes between the peripheral and central auditory system (Dehmel et al, 2012;Gu et al, 2012;Lowe and Walton, 2015), which may be explained by "synaptopathy/hidden hearing loss, " or damage to the peripheral afferent system in the absence of significant hair cell loss (Schaette and McAlpine, 2011;Kujawa and Liberman, 2015). Growing evidence suggests that SGNs or their synapses are preferentially targeted by AGs (Liu et al, 2013;Hong et al, 2018) which has also been shown to be true in histological analysis from human cadavers (Sone et al, 1998;Pauna et al, 2017). Importantly, mechanistic understandings of the peripheral and central issues related to AG treatment should be elucidated further.…”
Section: Clinical Relevance and Future Studiescontrasting
confidence: 52%
See 2 more Smart Citations
“…Although we did not observe significant synapse degradation/loss, we did observe changes in ABR wave III/I ratios indicating physiological changes between the peripheral and central auditory system (Dehmel et al, 2012;Gu et al, 2012;Lowe and Walton, 2015), which may be explained by "synaptopathy/hidden hearing loss, " or damage to the peripheral afferent system in the absence of significant hair cell loss (Schaette and McAlpine, 2011;Kujawa and Liberman, 2015). Growing evidence suggests that SGNs or their synapses are preferentially targeted by AGs (Liu et al, 2013;Hong et al, 2018) which has also been shown to be true in histological analysis from human cadavers (Sone et al, 1998;Pauna et al, 2017). Importantly, mechanistic understandings of the peripheral and central issues related to AG treatment should be elucidated further.…”
Section: Clinical Relevance and Future Studiescontrasting
confidence: 52%
“…Interestingly, a follow-up study found that these synapses partially repair after the cessation of AG treatment (Liu et al, 2015). Recent investigations suggest this phenomenon can be explained by AMPA and NMDA receptor reorganization following glutamate excitotoxicity (Hong et al, 2018). It was shown that partially preventing such glutamate hyperexcitability from both noise and amikacin via NMDA antagonists could prevent ribbon synapse damage in mice and guinea pigs (Duan et al, 2000;Hong et al, 2018).…”
Section: Temporary Threshold Shifts In the Absence Of Detectable Hairmentioning
confidence: 99%
See 1 more Smart Citation
“…Some NMDA antagonists have been used to investigate the protective effect in the inner ear using animal models of noise [ 11 , 12 , 14 ], ischemia [ 17 , 26 , 27 ], and ototoxicity [ 10 , 12 , 28 ]. Jäger et al demonstrated that dizocilpine maleate (MK-801) had a protective effect against NIHL, but the effect was limited to a specific frequency [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a recent mechanism of SNHL is reported to be related with cochlear or auditory synaptopathy, which is caused by damage or loss to the synapses between inner hair cell (IHC) and spiral ganglion neuron (SGN) and causing deafferentation [ 5 , 6 , 7 , 8 ]. Cochlear synpatopathy is also involved in genetic, noise, ototoxicity and age-related hearing loss [ 7 , 8 , 9 , 10 ]. This mechanism may contribute to glutamate excitotoxicity involving N -methyl- d -aspartate (NMDA) receptor activation and related auditory nerve excitation [ 9 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%